Encoding-Aware Data Placement for Efficient Degraded Reads in XOR-Coded Storage Systems: Algorithms and Evaluation - Shen, Zhirong; Lee, Patrick P. C.; Shu, Jiwu; Guo, Wenzhong (IEEE transactions on parallel and distributed systems, 2018)
Modern storage systems adopt erasure coding to maintain fault tolerance with low storage redundancy. However, how to improve the performance of degraded reads in erasure-coded storage has been a critical issue. We revisit this problem from two different perspectives that are neglected by existing studies: data placement and encoding rules. To this end, we propose encoding-aware data placement (EDP), which mitigates the number of I/Os in degraded reads during a single failure for general XOR-based erasure codes. EDP carefully selects appropriate parity units to be generated by sequential data based on the encoding rules and establishes their generation orders. We further refine the data placement for optimizing the degraded reads to any two sequential data units. Trace-driven evaluation results show that EDP significantly reduces I/Os in degraded reads and hence shortens the read time.